2019
DOI: 10.1021/acs.jpcb.9b07828
|View full text |Cite
|
Sign up to set email alerts
|

Designing Catalytic Sites on Surfaces with Optimal H-Atom Binding via Atom Doping Using the Inverse Molecular Design Approach

Abstract: It remains a general challenge to computationally design optimal catalytic structures based on earth-abundant metals for hydrogenation. Here, we demonstrate an effective computational approach based on inverse molecular design to deterministically design optimal catalytic sites on the Cu(100) surface through the doping of Fe and/or Zn, and a stable Zn-doped Cu(100) surface was found with minimal binding energy to H atoms. By the calculations at the level of density functional theory, the optimized catalyst sit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Tailoring the catalyst surface is the most common way to steer activity and selectivity to favor CO 2 RR over HER. , Many recent studies, however, have showed the importance of the electrolyte composition on the reaction rate of CO 2 reduction and H 2 evolution. Recently, Monteiro et al showed that the electrochemical reduction of CO 2 to CO on gold, copper, and silver electrodes requires the presence of a cation to coordinate and, hence, to stabilize the first electron-transfer intermediate CO 2 – . Nevertheless, an intermediate cation concentration is preferable, as cations also promote the concomitant water and bicarbonate reduction, favoring hydrogen evolution. ,,, Therefore, if water is the main proton donor, the activity for the hydrogen evolution reaction can be altered by changing the cation and its interfacial concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring the catalyst surface is the most common way to steer activity and selectivity to favor CO 2 RR over HER. , Many recent studies, however, have showed the importance of the electrolyte composition on the reaction rate of CO 2 reduction and H 2 evolution. Recently, Monteiro et al showed that the electrochemical reduction of CO 2 to CO on gold, copper, and silver electrodes requires the presence of a cation to coordinate and, hence, to stabilize the first electron-transfer intermediate CO 2 – . Nevertheless, an intermediate cation concentration is preferable, as cations also promote the concomitant water and bicarbonate reduction, favoring hydrogen evolution. ,,, Therefore, if water is the main proton donor, the activity for the hydrogen evolution reaction can be altered by changing the cation and its interfacial concentration.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is challenging to incorporate geometric stability into inverse molecular design methods. Indeed, although applications of extended tight-binding LCAP to catalyst designs using fixed molecular structures have been reported, , such a scheme requires careful preparation of the chemical space and validation of the stability of both the designed structures and the properties by extra geometry optimization after the design. The inverse design methods should provide functional molecules in their equilibrium structures.…”
mentioning
confidence: 99%
“…The huge computational costs of the ab initio methods hinder these applications to the large chemical space. To overcome this problem, the LCAP was implemented using the semiempirical AM1, Hückel, and extended Hückel methods. , These LCAP strategies were successfully utilized in the design of nonlinear optical molecules, , inhibitors for redox regulation, dye-sensitized solar cells, molecular catalysts, and catalytic sites on the metal surface and in atomic configuration search of alloys …”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the LCAP was implemented using the semiempirical AM1, Huckel, and extended Huckel methods. 33,34 These LCAP strategies were successfully utilized in the design of nonlinear optical molecules, 24,33−37 inhibitors for redox regulation, 38 dyesensitized solar cells, 39 molecular catalysts, 40 and catalytic sites on the metal surface 41 and in atomic configuration search of alloys. 42 The Frenkel exciton model has been widely adopted to describe and interpret photophysical phenomena of molecular aggregates, including the absorption and CD.…”
Section: Introductionmentioning
confidence: 99%